2006
DOI: 10.1227/01.neu.0000209034.86039.39
|View full text |Cite
|
Sign up to set email alerts
|

Single-Stage Thoracolumbar Vertebrectomy With Circumferential Reconstruction And Arthrodesis: Surgical Technique And Results In 15 Patients

Abstract: The authors present a method for thoracolumbar vertebrectomy, circumferential reconstruction, and arthrodesis performed in a single stage, solely via a posterior approach. This is an alternative to anterior (i.e., thoracoabdominal and retroperitoneal) and lateral (i.e., lateral extracavitary) approaches that can be used for circumferential reconstruction and arthrodesis. Potential advantages and pitfalls are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 23 publications
3
41
0
4
Order By: Relevance
“…3,7,10,11 Because of advances in surgical techniques and surgeon comfort, thoracolumbar corpectomies are increasingly performed via a posterior approach. 1,8,9,12,13,16 In our study, we found similar morbidity for the anterior-only and transpedicular approaches with regard to complication rate, EBL, and operative time. However, performing an anterior-posterior approach increased the morbidity much more than the transpedicular approach, with increasing EBL (3154 vs 1857 ml), longer mean surgical times (729 vs 450 minutes), and slightly higher complication rates (41 vs 29%, respectively, although not statistically significant).…”
Section: Discussionsupporting
confidence: 73%
“…3,7,10,11 Because of advances in surgical techniques and surgeon comfort, thoracolumbar corpectomies are increasingly performed via a posterior approach. 1,8,9,12,13,16 In our study, we found similar morbidity for the anterior-only and transpedicular approaches with regard to complication rate, EBL, and operative time. However, performing an anterior-posterior approach increased the morbidity much more than the transpedicular approach, with increasing EBL (3154 vs 1857 ml), longer mean surgical times (729 vs 450 minutes), and slightly higher complication rates (41 vs 29%, respectively, although not statistically significant).…”
Section: Discussionsupporting
confidence: 73%
“…The stabilization of the posterior blade allows the anterior blades to be safely deployed to create sufficient access space for discectomy (Figure 3d), corpectomy and implant placement. The exhibition allows direct visualization of the lateral side facilitating the disc discectomy (Figure 3d), corpectomy, and the placement of a prosthetic vertebral body expansion and bone grafting [10]. Discectomies (Figure 3d) are performed both cephalad and caudal to the fracture using a scalpel to incise the anular tissue and a pituitary rongeur or curette to extract the disk material.…”
Section: First Surgical Approach Retroperitoneal Dissectionmentioning
confidence: 99%
“…Other indications include the resection of hemivertebrae 4,16 or intravertebral spinal tumors, 1,10,31,37,39 or even, as has recently been described, the shortening of the spine proximal to a tethered region as a novel method of treating tethered spinal cord without the risks of dissection around adhesed nerve roots. 4,12,17 Outcomes After Surgery Studies of pVCR to date have demonstrated it to be a powerful method of focal deformity correction.…”
Section: Surgical Techniquementioning
confidence: 99%